Reflecting on Eliud Kipchoge`s marathon world record: An update to our model of cooperative drafting and its potential for a sub-2-hour performance - Hoogkamer, W.; Snyder, K. L.; Arellano, C. J. (Sports Medicine, 2019)
As sports enthusiasts and scientists, we were reminded of many important lessons on the day that Eliud Kipchoge set a new world record in the marathon. On September 16th, 2018, he ran a time of 2:01:39 in Berlin, eclipsing the previous record by 1 min and 18 s. Two days before the Berlin marathon race was to take place, our paper [1] was accepted, but would not be seen in press until a week later. On the day of the race, Kipchoge not only broke the world record, but he might have also broken the record for outdating a scientific paper. Note that for our simulations of cooperative drafting during marathon running, we used Kipchoge`s fastest marathon time (2:03:05 from the London marathon in April 2016) as a model input. Kipchoge`s new world record time suggests that since he is so much faster than any other current or historical marathon runner, he might not be able to benefit from cooperative drafting as we originally predicted. Kipchoge`s new world record time also...